Introducing the Worldwide Incidents Tracking System (WITS) - John Wigle (Perspectives on Terrorism)
For researchers looking for an authoritative data source on terrorist attacks: The Worldwide Incidents Tracking System (WITS) is the U.S. Government's authoritative database on acts of terrorism, and is used to enumerate statistical data for the annual publications Country Reports on Terrorism (from the U.S. Department of State) and the NCTC Report on Terrorism. This article provides a brief tutorial on WITS and, by way of example, a cursory look at trends in terrorism lethality.